Aplikasi Kamus Online Bahasa Indonesia-Tanjungbalai Berbasis Web Menggunakan Metode Squential Search - Muhaimin Iskandar; Rahmat Aulia; Tasliyah Haramaini (INCODING: Journal of Informatics and Computer Science Engineering, 2022)
Humans can interact with each other through language. Indonesia is a heterogeneous country that has a variety of cultures, where each region has its own regional language. Tanjungbalai Malay is one of the many regional languages in Indonesia which includes the city of Tanjungbalai and several areas in the Asahan district. Along with the development of the times, the use of the Tanjungbalai Malay language has decreased. In fact, it is not uncommon, especially from young people who do not know their own regional language. The lack of interesting media and motivates people to learn regional languages is one of the reasons why regional languages have decreased speakers. With the application of this web-based Indonesian–Tanjungbalai online dictionary, it is hoped that it will facilitate and be a stimulus for people especially those living in the city of Tanjungbalai in learning the regional language of the city of Tanjungbalai, so that speakers of the local language of Tanjungbalai in the city of Tanjungbalai do not experience extinction. This application is built by applying sequential search method for word searching. The search process in this method is to match the data in a row starting from the first data until the data sought is found.